Cybersex and Religion: Intimacy, Resistance, and Negotiation of Islamic Students In Indonesia - Radius Setiyawan; Sri Lestari; Arin Setiyowati (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2022)
This article focused on the teenage generation and religion as the dominant sources of truth in Indonesia, especially Islam. Religion rules become a norm that is upheld and fought for. This article explained how the generation of teenagers in Surabaya who have the same background at Islamic Universities. They used to apply virtual spaces related to sexual activities. Apart from that, this paper also tried to relate their practice to the religious teachings they profess. The informants of this study were students at several universities in Surabaya. Those who become informants were students, consisting of males and females, who openly admitted to having the habit of engaging in sexual activities in cyberspace. This research aimed to explain the practices of resistance and negotiation that occur on religious teachings. The data collection method used was in-depth interviews which focused on how they used virtual space relating to sexuality. There were various entrances to various forms of sexual simulacrums and sexuality within cyberspace, various sexual acts, and the scene that